Propulsion Mechanics - BOUKHARI Ali (University of Eloued, 2023)
Propulsion mechanics is a crucial domain in aerospace engineering and vehicle technology. This course material delves into the fundamental principles of reaction propulsion, with a focus on the performance of aviation engines. Through detailed analysis, it examines the characteristics and applications of ramjets, turbojets, and rocket engines. The introduction provides essential context for understanding these concepts, while each section explores in-depth the mechanisms and performance of each engine type. This document aims to offer a comprehensive understanding of propulsion mechanics and its importance in the aerospace field. La mécanique de propulsion est un domaine crucial de l'ingénierie aérospatiale et de la technologie des véhicules. Cette brochure explore en profondeur les principes fondamentaux de la propulsion par réaction, en mettant l'accent sur les performances des moteurs d'aviation. À travers une analyse détaillée, elle examine les caractéristiques et les applications des statoréacteurs, des turboréacteurs et des moteurs de fusées. L'introduction fournit un contexte essentiel pour comprendre ces concepts, tandis que chaque section explore en détail les mécanismes et les performances de chaque type de moteur. Ce document vise à offrir une compréhension approfondie de la mécanique de propulsion et de son importance dans le domaine de l'aérospatiale.
مطبوعة بيداغوجية موجهة لطلبة سنة ثانية ماستر طاقوية
Keywords: Propulsion mechanics; Jet propulsion; Ramjets; Turbojets; Rocket engines.